Electrochromic intelligent window and preparation method thereof

By using a symmetrical structural design of niobium-substituted heteropolytungstates and aluminum-zinc salt electrolytes in electrochromic smart windows, the film-forming and interface compatibility problems of traditional electrochromic smart windows are solved, and the synergistic effect of electrochromism and energy storage with high optical modulation capability and wide spectral response is achieved, thereby improving the cycle stability and durability of the device.

CN120595522AActive Publication Date: 2025-09-05厦门工学院
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511107037.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-09-05
Estimated Expiration
2045-08-08

AI Technical Summary

Technical Problem

Traditional electrochromic smart windows have problems such as poor material film forming and interface compatibility, single color change, slow response speed, insufficient cycle stability, and difficulty in balancing high optical modulation rate. In addition, the traditional multi-layer structure increases device complexity and interface problems.

Method used

Niobium-substituted heteropolytungstate is used as the electrochromic layer, combined with liquid electrolytes of aluminum salt and zinc salt. Through symmetrical structural design, the charge transfer path is optimized, and a counter electrode is introduced into the device to improve ionic conductivity and optical modulation ability, thereby achieving a synergistic effect of electrochromism and energy storage functions.

Benefits of technology

The optical modulation amplitude and response speed of the smart window are improved, the optical modulation range is broadened to the ultraviolet-visible-near-infrared wide band, the cyclic stability and durability of the device are enhanced, the device architecture is simplified, and high contrast and wide spectral response are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120595522A_ABST
    Figure CN120595522A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building intelligent windows, and provides an electrochromic intelligent window and a preparation method thereof. The electrochromic intelligent window comprises a first working electrode, a second working electrode and an ionic conducting medium layer, wherein the first working electrode and the second working electrode are oppositely arranged; the first working electrode and the second working electrode respectively comprise a first electrochromic layer and a second electrochromic layer; the ionic conducting medium layer comprises an electrolyte layer formed by liquid electrolyte and a counter electrode, the first electrochromic layer and the second electrochromic layer contain polyacid, and the liquid electrolyte contains aluminum salt and zinc salt. The intelligent window has the characteristics of high contrast ratio, high cycling stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building smart windows, and in particular, provides an electrochromic smart window and a preparation method thereof. Background Art

[0002] Electrochromism refers to the process of changing the color of a substance by applying an external electric field. + 、Li + During the injection or removal of positive ions (such as cations) from the material, an electrochemical reaction occurs, causing the material's optical properties, such as transmittance, absorbance, or reflectance, to exhibit persistent and reversible changes. This change is not limited to the visible light range observable to the naked eye, but also includes the ultraviolet light band, the infrared light band, and most electromagnetic wave bands. In recent years, electrochromic technology has attracted much attention due to its unique advantages: on the one hand, the color of the material can be easily controlled by simply adjusting the voltage; on the other hand, the technology combines non-volatility (memory effect) with low energy consumption; and most importantly, its optical response has excellent reversibility and cyclic stability. These characteristics give electrochromic technology broad application prospects in smart displays, automotive anti-glare rearview mirrors, building energy-saving dimming windows (such as smart glass), and other fields.

[0003] Traditional electrochromic smart windows are generally symmetrical sandwich structures, including a first transparent substrate layer, a first transparent conductive layer, an electrochromic layer, an electrolyte layer, an ion storage layer, a second transparent conductive layer, and a second transparent substrate layer stacked in sequence. Among them, the electrochromic layer is the core layer, and the electrochromic material therein undergoes an oxidation-reduction reaction under voltage drive to produce a reversible color change; the electrolyte layer is a pure ion conductor, usually containing a solution or solid electrolyte material of a perchlorate (such as lithium perchlorate, sodium perchlorate, etc.); the ion storage layer mainly balances the charge and stores counter ions when the electrochromic material undergoes an oxidation-reduction reaction. Usually, the electrolyte layer adopts a single perchlorate system, but in electrochromic applications, this type of system based on monovalent cations (such as 、 、 ) electrolytes still have significant limitations: for example, Corrosive, Resource reserves are limited and the cost is high. The large ionic radius results in slow intercalation and deintercalation kinetics within the material. Furthermore, the ion storage layer must possess complementary optical properties to the electrochromic layer (typically remaining colorless) to enable effective charge compensation when the latter changes color. This traditional multilayer structure, comprising multiple independent functional layers, not only increases device complexity but also serves as the structural root cause of the aforementioned limitations of the electrolyte and ion storage layer, thereby limiting further performance improvements and application expansion of electrochromic devices.

[0004] Electrochromic smart windows typically rely on metal oxide materials (such as WO3) as the core color-changing layer. However, these materials face numerous challenges in practical applications: a single color change (primarily blue), slow response speed, insufficient cycling stability, and difficulty in achieving both high optical modulation rate and excellent electrochemical reversibility. Furthermore, as mentioned above, conventional structures require complex multilayer stacking to achieve device functionality, which introduces interfacial issues and hinders device performance and scalable application.

[0005] Polyoxometalates (POMs) are a class of inorganic clusters with a well-defined metal-oxygen framework. Their excellent structural stability, rich multi-electron reversible redox properties, tunable molecular composition, and high intrinsic electrochemical activity make them promising electrochromic materials. Of particular note, the inherent pseudocapacitive properties of POMs make them uniquely valuable for integrating electrochromism with energy storage. However, the effective application of POM-based materials in high-performance electrochromic devices still requires addressing the following key issues: 1) Poor film-forming properties and interfacial compatibility: Pure POMs are difficult to directly form uniform, dense, and strongly adherent functional films on common substrates, and their long-term interfacial stability with adjacent functional layers is challenging. 2) Limited optical properties in the colored state: Most POMs exhibit relatively limited hues in their reduced (colored) state, making them inadequate for achieving broadband, tunable, multicolor electrochromism. 3) Operating voltage and stability: Driving significant optical modulation in POMs typically requires high operating voltages, which can be associated with the risk of electrolyte side reactions and potentially impact the long-term cycling stability of the device. Summary of the Invention

[0006] The present invention aims to provide an electrochromic smart window and a method for preparing the same. The electrochromic smart window of the present invention is a polyacid-based electrochromic smart window having the characteristics of high contrast and high cycle stability.

[0007] In a first aspect, the present invention provides an electrochromic smart window, comprising: a first working electrode and a second working electrode disposed opposite to each other, and an ion conductive medium layer located therebetween; The first working electrode comprises a first transparent substrate, a first transparent conductive layer and a first electrochromic layer stacked in sequence; The second working electrode comprises a second transparent substrate, a second transparent conductive layer and a second electrochromic layer stacked in sequence; The ion conductive medium layer comprises: an electrolyte layer formed of a liquid electrolyte, the liquid electrolyte occupying a space between the first electrochromic layer and the second electrochromic layer and contacting the first electrochromic layer and the second electrochromic layer, respectively; and a counter electrode, comprising two metal sheets, the two metal sheets being disposed at opposite ends of the electrolyte layer and spaced apart from each other, each metal sheet having a main section and an extension section, the main section being embedded within the electrolyte layer, and the extension section extending from the electrolyte layer; The first electrochromic layer and the second electrochromic layer both contain polyacids, and the polyacids are heteropolytungstates substituted with niobium; the liquid electrolyte further contains aluminum salt and zinc salt.

[0008] As some preferred embodiments, the thickness of the first electrochromic layer and the second electrochromic layer are independently 5-7 μm.

[0009] In a second aspect, the present invention provides a method for preparing the electrochromic smart window according to the first aspect of the present invention, comprising the following steps: (1) Preparation of the first working electrode and the second working electrode Providing a first transparent substrate having a first transparent conductive layer formed on its surface and a second transparent substrate having a second transparent conductive layer formed on its surface; applying a precursor solution containing the polyacid on the surfaces of the first transparent conductive layer and the second transparent conductive layer respectively to form a first electrochromic layer and a second electrochromic layer; (2) Constructing an ion conductive medium layer applying the liquid electrolyte on the surfaces of the first electrochromic layer and the second electrochromic layer respectively to form an electrolyte layer between the first electrochromic layer and the second electrochromic layer; A metal sheet is embedded in the opposite ends of the electrolyte layer respectively, so that each metal sheet has a main section and an extension section to obtain a counter electrode.

[0010] The electrochromic smart window of the present invention features a symmetrical structural design centered around an ion-conducting dielectric layer. This design utilizes aluminum and zinc salts as the primary components of the electrolyte layer, enhancing ionic conductivity and improving the optical modulation amplitude of the smart window. The electrochromic layer, in contact with the electrolyte, utilizes a niobium-substituted heteropolytungstate as the color-changing material. Its multi-electron redox properties effectively improve coloring efficiency and optical response speed, significantly broadening the optical modulation range to a wide UV-visible-near-infrared band (350-1300 nm). Furthermore, in the smart window of the present invention, the counter electrode (two metal plates) is located in the center of the device (i.e., the smart window), with working electrodes flanking it. This layout optimizes the charge transfer pathway. The aluminum and zinc salts acting as electrolytes synergistically with the niobium-substituted heteropolytungstate significantly improve the device's charge storage capacity and ion transport kinetics. This combination not only enhances the optical modulation capability (high contrast and a wide spectral range), but also achieves a synergistic effect between electrochromism and energy storage, resulting in high cycling stability.

[0011] In addition, compared with traditional tungsten trioxide smart windows (relying on complementary electrodes and magnetron sputtering technology) and polymer-based smart windows (insufficient cyclic stability), the present invention simplifies the device architecture through a symmetrical structure (no need for complex complementary electrodes and sputtering equipment) while maintaining the device's color-changing performance. Relying on the synergistic effect of materials, it significantly improves durability and has both wide spectral response and energy storage functions, providing a new direction for the development of smart windows and energy integrated devices.

[0012] Additional aspects and advantages of the present invention will be set forth in part in the description which follows and, in part, will be obvious from the description which follows, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments with reference to the following drawings, in which: Figure 1 The polyacid {P2W 15 Physical diagram of Nb3}; Figure 2 The polyacid {P2W prepared in Preparation Example 1 15 Thermogravimetric diagram of Nb3}; Figure 3 is a diagram of the electrochromic structure of an electrochromic smart window according to one embodiment of the present invention; Figure 4 A schematic diagram of the structure of the ion conductive medium layer and a schematic diagram of the conductive connector connected to the electrode according to one embodiment of the present invention; Figure 5 Schematic diagram illustrating reversible conversion between tinted and transparent electrochromic smart window according to one embodiment of the present invention; Figure 6 This is a photo of the electrochromic smart window of Example 1 reversibly switching between colorless and blue; Figure 7 is a scanning electron microscope image showing the morphology of the electrochromic layer in the electrochromic smart window of Example 1; Figure 8 is the electrochemical impedance spectroscopy of the electrochromic layer of Example 1; Figure 9 1 is the cyclic voltammogram of the electrochromic smart window of Example 1; Figure 10 This is the constant current charge and discharge spectrum of the electrochromic smart window of Example 1; Figure 11 This is a graph showing the transmittance spectrum change corresponding to the electrochromic smart window of Example 1 when it undergoes a reversible conversion between colorless and blue; Figure 12Response time diagram of the reversible conversion of the electrochromic smart window of Example 1 between colorless and blue; Figure 13 This is a transmittance change diagram of the electrochromic smart window of Example 1 when it is reversibly switched between colorless and blue for 50,000 seconds.

[0014] Description of Reference Numerals 100: electrochromic smart window; 10: first working electrode; 20: second working electrode; 30: ion conductive medium layer; 11: first transparent substrate; 12: first transparent conductive layer; 13: first electrochromic layer; 21: second transparent substrate; 22: second transparent conductive layer; 23: second electrochromic layer; 31: electrolyte layer; 32: counter electrode; 32a: main section; 32b: extension section; 40: conductive connector. DETAILED DESCRIPTION

[0015] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0016] The "ranges" disclosed herein are defined in terms of lower and / or upper limits, with a given range being defined by selecting a lower limit and / or an upper limit. Ranges defined in this manner may be inclusive or exclusive of the end values ​​and may be combined arbitrarily, i.e., any lower limit may be combined with any upper limit to form an unspecified range, and any lower limit may be combined with any other lower limit to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value may itself be combined as a lower limit or upper limit with any other point or single value, or with other lower limits or upper limits to form an unspecified range.

[0017] In the present invention, the terms "first", "second" and "I" and "II" are only used for distinction and convenience of description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.

[0018] In the present invention, unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present invention.

[0019] The present invention provides an electrochromic smart window. According to some embodiments, Figure 3 and Figure 4 As shown, the electrochromic smart window 100 includes a first working electrode 10 and a second working electrode 20 that are arranged opposite to each other, and an ion conductive medium layer 30 located therebetween, wherein: The first working electrode 10 includes a first transparent substrate 11, a first transparent conductive layer 12, and a first electrochromic layer 13 stacked in sequence. The second working electrode 20 includes a second transparent substrate 21, a second transparent conductive layer 22, and a second electrochromic layer 23 stacked in sequence. The ion conductive medium layer 30 includes: The electrolyte layer 31 is formed of a liquid electrolyte, which occupies the space between the first electrochromic layer 13 and the second electrochromic layer 23 and contacts the first electrochromic layer 13 and the second electrochromic layer 23 respectively; The counter electrode 32 is composed of two metal sheets, which are respectively arranged at opposite ends of the electrolyte layer 31 and spaced apart from each other. Each metal sheet has a main section 32a and an extended section 32b. The main section 32a is embedded in the interior of the electrolyte layer 31, and the extended section 32b extends from the electrolyte layer 31.

[0020] In the present invention, the first electrochromic layer and the second electrochromic layer both contain polyacids, and the polyacids are niobium-substituted heteropolytungstates, for example, niobium trisubstituted Dawson-type tungstophosphates. Preferably, the niobium-substituted heteropolytungstates are K8H[P2W 15 (N b O2)3O 59 ]·12H2O.

[0021] Preferably, the first and second electrochromic layers further include TiO2 distributed therein. TiO2 is typically used as a carrier to improve the film-forming properties of the polyacid. TiO2 is in the form of fine particles (typically microspheres), which, when distributed within the electrochromic layer, increase the specific surface area of ​​the electrochromic layer. Furthermore, the TiO2 particle surface is rich in hydroxyl groups, which can form hydrogen bonds with oxygen atoms or proton donors in the polyacid molecules, effectively fixing the polyacid on the TiO2 surface and achieving the stable construction of the polyacid film (i.e., the electrochromic layer).

[0022] Preferably, the thickness of the first electrochromic layer and the second electrochromic layer are independently 5 to 7 μm, for example, 5 μm, 5.5 μm, 6 μm, 7 μm, etc. In this case, on the one hand, it can avoid the electrochromic layer being too thin and affecting the overall performance of the smart window, and on the other hand, it can also reduce the possibility of the electrochromic layer being too thick and causing the film to fall off. More preferably, the thickness of the first electrochromic layer and the second electrochromic layer are the same. In the present invention, the electrolyte layer is formed from a liquid electrolyte containing aluminum and zinc salts. Compared to traditional alkali metal salt electrolytes (such as lithium and sodium salts), aluminum and zinc salts offer lower costs and higher safety. Preferably, the aluminum salt is aluminum perchlorate (Al(ClO4)3), and the zinc salt is zinc perchlorate (Zn(ClO4)2).

[0023] As a preferred embodiment, the molar ratio of the aluminum salt to the zinc salt is 1:(0.8-1.2), such as 1:0.8, 1:0.9, 1:1, 1:1.1, or 1:1.2. This ratio helps reduce the possibility of shortening the service life of the smart window due to a relative excess of aluminum salt, while minimizing the risk of prolonged response time due to an excess of zinc salt.

[0024] In the present invention, the liquid electrolyte may further comprise a solvent, and the solvent is preferably an organic solvent. The use of an organic solvent can reduce the hydrolysis of polyacids and prevent Al 3+ and Zn 2+ The precipitation plays a role in protecting the conductive layer, thereby improving the cycle stability of the device. More preferably, the organic solvent is selected from at least one of propylene carbonate (PC), ethylene carbonate (EC), and acetonitrile (ACN).

[0025] In some embodiments, the total concentration of aluminum salt and zinc salt in the liquid electrolyte is 0.8~1.5 mol / L, for example, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, etc.

[0026] In some embodiments, the thickness of the ion conductive medium layer (ie, the thickness of the electrolyte layer) is 1-2.5 mm, for example, 1 mm, 1.2 mm, 1.4 mm, 1.5 mm, 1.8 mm, 2 mm, 2.5 mm, etc.

[0027] In the present invention, the counter electrode comprises two metal sheets. The present invention does not particularly limit the metal sheets and can be selected based on existing smart windows. For example, the metal sheets can be selected from various conductive metal foils, with specific examples including, but not limited to, zinc foil, copper foil, and nickel foil. According to some embodiments, the thickness of the metal sheets is 20 to 60 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 55 μm, 60 μm, etc.

[0028] In the present invention, two metal sheets can be arranged in parallel with the first electrochromic layer and the second electrochromic layer (the angle between the metal sheet and one of the electrochromic layers is ≤5°). In addition, the metal sheet can be inserted into the electrolyte layer in a manner that its long axis direction is perpendicular to the embedding path (the direction from the end to the middle of the electrolyte layer), or it can be inserted into the electrolyte layer in a manner that its short axis direction is perpendicular to the embedding path. The main section is defined as the effective area where the metal sheet is in complete macroscopic contact with the liquid electrolyte, and the exposed areas that are not in contact with the liquid electrolyte are collectively referred to as extended sections for external connection to wires. The extended section can also be a single area or multiple areas. Since the metal sheet is conductive as a whole, it is only necessary to select any extended area for connection. According to some embodiments, such as Figure 4 As shown in the figure, A and B are respectively a cross-sectional view and a top view of the ion-conductive dielectric layer, and C shows two segments of a single metal sheet. As can be seen from A to C, a portion of the metal sheet is embedded in the electrolyte layer 31. The embedded portion is the main segment 32a, and the area exposed outside the electrolyte layer 31 is the extended segment 32b. Typically, the total area of ​​the main segments of the two metal sheets can be 20% to 50% of the light-emitting area of ​​the smart window.

[0029] The present invention does not particularly limit the transparent substrate; it can be selected based on existing smart windows. In some embodiments, both the first and second transparent substrates are glass. Preferably, the material of the first and second transparent conductive layers is independently selected from at least one of indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), and antimony-doped tin oxide (ATO).

[0030] In some embodiments, the thickness of the first transparent conductive layer and the second transparent conductive layer may be 0.1-1 μm, for example, 0.1 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.7 μm, 0.8 μm, etc.

[0031] In some embodiments, the ratio of the thickness of the first transparent substrate, the first transparent conductive layer, and the first electrochromic layer 13 is (200-400):(0.02-0.1):1.

[0032] In some embodiments, a ratio of the thicknesses of the second transparent substrate, the second transparent conductive layer, and the second electrochromic layer is (200-400):(0.02-0.1):1.

[0033] As a preferred embodiment, the first working electrode and the second working electrode are the same, that is, the composition and thickness of each layer are the same.

[0034] In the smart window structure of the present invention, a common counter electrode is provided between two working electrodes arranged opposite to each other, forming a dual electrochromic circuit parallel structure, thereby achieving coordinated color change of the two electrochromic layers. Figure 5 As shown, its working method can be: applying voltage drives electrolyte ions to embed into the electrochromic layer, causing coloration; after reversing the voltage polarity, the ions are released and the electrochromic layer returns to a transparent state, thus achieving reversible optical control. In addition, because the two electrochromic layers can achieve synchronous response under the same bias voltage, their superposition effect can achieve a more optimized overall optical modulation effect.

[0035] The present invention also provides a method for preparing the electrochromic smart window, comprising the following steps: (1) Preparation of the first working electrode and the second working electrode Providing a first transparent substrate having a first transparent conductive layer formed on its surface and a second transparent substrate having a second transparent conductive layer formed on its surface; applying a precursor solution containing the polyacid on the surfaces of the first transparent conductive layer and the second transparent conductive layer respectively to form a first electrochromic layer and a second electrochromic layer; (2) Constructing an ion conductive medium layer applying a liquid electrolyte on the surfaces of the first electrochromic layer and the second electrochromic layer, respectively, to form an electrolyte layer between the first electrochromic layer and the second electrochromic layer; A metal sheet is embedded in the opposite ends of the electrolyte layer respectively, so that each metal sheet has a main section and an extension section to obtain a counter electrode.

[0036] In step (1), the precursor solution can be applied to the conductive layer by electrochemical deposition or coating to form the electrochromic layer. When electrochemical deposition is used, the precursor solution is an electrodeposition solution; when coating is used, the precursor solution is a coating solution. The specific formulations of the electrodeposition solution and the coating solution are determined according to the respective process requirements, and their conventional compositions are well known in the art.

[0037] As a preferred embodiment, the first and second electrochromic layers are formed using chemical electrodeposition. In this case, the precursor solution is a deposition solution containing the polyacid; wherein the deposition solution also contains water and an electrolyte salt. The electrolyte salt can be selected from at least one of lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4). In the deposition solution, the polyacid concentration can be 0.5 to 2 mmol / L, for example, 0.5 mmol / L, 1 mmol / L, 1.2 mmol / L, 1.5 mmol / L, etc., and the electrolyte salt concentration can be 0.05 to 2 mol / L, for example, 0.05 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, etc.

[0038] Furthermore, step (1) includes the following process: First, a TiO2 matrix layer is formed on the surface of the first transparent conductive layer and the second transparent conductive layer respectively to obtain a deposited working electrode; Then, each deposition working electrode is placed in a precursor solution containing polyacid (i.e., deposition solution), a voltage of -1V to 0.3V is applied, and a scan rate of 0.05~0.1V / s is cyclically scanned for 10~50 times to form polyacid on the TiO2 matrix layer, thereby obtaining the first electrochromic layer and the second electrochromic layer.

[0039] TiO2 slurry can be applied to the conductive layer via doctor blade coating or screen printing to form a wet film. The film is then sintered at 450-550°C for 0.5-1.5 hours. The slurry solidifies to form a transparent thin film (i.e., the TiO2 matrix layer). The TiO2 slurry can have a solids content of 15%-25%, and a wet film thickness of 20-40 μm. TiO2 slurry is commercially available, for example, from Dyesol under the designation 18NR-T. Deposition is performed using cyclic voltammetry on an electrochemical workstation. The reference electrode used can be an Ag / AgCl electrode, and the counter electrode used for deposition can be a platinum sheet.

[0040] In step (2), the liquid electrolyte may be applied by injection or coating to form an electrolyte layer between the first electrochromic layer and the second electrochromic layer. Preferably, the electrolyte layer is formed by coating.

[0041] Preferably, step (2) includes the following process: A liquid electrolyte is evenly coated on the surface of the electrochromic layer of each working electrode to form an electrolyte coating. Two sets of working electrodes with electrolyte coatings are placed face-to-face, with the coatings facing and in contact, to form an electrolyte layer. Two conductive metal foils are used as counter electrodes. The metal foils are inserted into the electrolyte layer from the ends, ensuring a continuous electrolyte layer (i.e., the two metal foils are arranged with an interval between them), thereby forming an ionically conductive dielectric layer.

[0042] In some embodiments, the preparation method of the present invention further comprises: (3) External electrode formation and device packaging First and second conductive connectors are disposed at the edges of the first and second working electrodes, respectively, and a third conductive connector is disposed in the extended section of the metal sheet. Finally, the entire smart window is encapsulated with an encapsulating material (such as epoxy resin) to produce an electrochromic smart window with a symmetrical electrode structure. The conductive connectors may include copper foil conductive tape.

[0043] The following embodiments of the present invention are described. The following embodiments are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0044] Preparation Example 1 This preparation example is used to illustrate the polyacid K8H[P2W 15 (N b O2)3O 59 ]·12H2O and its preparation method.

[0045] 1) K6[α-P2W 18 O 62 ]·14H2O (abbreviated as "{P2W18 Preparation of Dissolve 100g of Na₂WO₄·2H₂O in water and heat to boiling. Slowly add 150mL of 85wt% phosphoric acid solution dropwise while stirring. The resulting yellow-green solution is stirred and refluxed for 12 hours. After the reaction is complete and the solution is cooled to room temperature, 100g of KCl is added, resulting in a large amount of precipitate. The precipitate is collected by filtration and redissolved in hot water. The solution is then allowed to stand at 5°C for 12 hours, allowing it to crystallize and then dry to obtain a crystalline product.

[0046] Take 70g of the above crystalline product and dissolve it in 250mL of hot water (water temperature is 80℃). Under stirring, add bromine water (0.05mL), and then cool the solution to room temperature. Under stirring, continue to add 10wt% KHCO3 aqueous solution (400mL) to the solution. It is observed that a precipitate is first generated in the solution. With continuous stirring, the precipitate dissolves and the solution becomes colorless and transparent. Add 110mL of hydrochloric acid (concentration is 6mol / L) to the resulting mixture to obtain a light yellow solution. Boil the solution for 1 hour and filter it. After filtration, add 100g of KCl to the solution and stir until it is completely dissolved. Then, let the resulting mixed solution stand at 5℃ for 12h to generate yellow crystals. After drying, collect the sample {P2W 18}.

[0047] (2) K 10 [α-P2W 17 O 61 ]·20H2O (abbreviated as "{P2W 17 Preparation of 80g sample {P2W 18} was dissolved in water, 250 mL of a 0.2 mol / L KHCO3 aqueous solution was added, and the mixture was stirred for 1 hour to generate a white precipitate, thereby obtaining a solid-liquid mixture. The solid-liquid mixture was filtered to recover the white precipitate, which was redissolved in boiling water and then cooled to room temperature to precipitate snowflake-like recrystallization. The recrystallized product was collected by filtration and dried to obtain a sample {P2W 17}.

[0048] (3) K7[P2W 17 (NbO2)O 61 ]·8H2O (abbreviated as "{P2W 17 Preparation of Nb}") 0.25g K7HNb6O 19 13H2O was dissolved in hydrogen peroxide (30 wt%) and 1 mol / L hydrochloric acid was added dropwise to adjust the pH of the solution to 1. Subsequently, 4.5 g of the sample {P2W 17} and continued stirring for 15 minutes, then added 20g KCl, a yellow solid precipitated, continued stirring for 10 minutes, filtered the yellow precipitate and recrystallized in water to obtain the sample {P2W 17 Nb}.

[0049] (4) Na 12 [P2W 15 O 56 ]·24H2O (abbreviated as "{P2W 15 Preparation of 38.5g of sample {P2W 18} was dissolved in water and 35g of NaClO4·H2O was added. The resulting system was vigorously stirred for 20 minutes to obtain a solution. The solution was further stirred in an ice-water bath for 3 hours and then filtered. A total of 100mL of a 1mol / L aqueous solution of Na2CO3 was added dropwise to the filtrate to form a white precipitate. The precipitate was filtered, washed and dried to obtain the product {P2W 15}.

[0050] (5) K8H[P2W 15 (NbO2)3O 59 ]·12H2O (abbreviated as "{P2W 15 Preparation of Nb3}") 0.8g K7HNb6O 19 13H2O was dissolved in hydrogen peroxide (30 wt%), and 1 mol / L hydrochloric acid was added dropwise to adjust the pH of the solution to 1 to obtain solution I.

[0051] 5g sample {P2W 15} was dissolved in 50 mL of 1 mol / L LiCl aqueous solution, and 1 mL of 1 mol / L hydrochloric acid was added dropwise to obtain solution II.

[0052] Solution I and solution II were mixed and stirred for 20 minutes, then 20 g of KCl was added, a yellow precipitate began to precipitate, and stirring was continued for 10 minutes, and the yellow precipitate was collected by filtration. The precipitate was added to hot water for recrystallization to obtain the target product {P2W 15 Nb3}.

[0053] like Figure 1 As shown, the {P2W 15 Nb3} is a yellow solid. Figure 2 It can be seen that the {P2W 15 Nb3} loses only 5% of its mass (crystallization water) at 600°C, which shows that it has very good thermal stability and is suitable for use in electrochromic devices.

[0054] The following examples refer to Figure 1The electrochromic smart window and its preparation method of the present invention are described as follows: TiO2 slurry was purchased from Dyesol Co., Ltd., with the brand name 18NR-T.

[0055] Example 1 S1: Two sets of working electrodes were prepared using the same process FTO conductive glass (specifications: 3.5 cm × 3.5 cm) was ultrasonically cleaned in water, acetone, and ethanol for 20 minutes each, and then dried with high-pressure nitrogen.

[0056] The TiO2 slurry was evenly coated on the FTO conductive layer of the conductive glass by screen printing, and the wet film thickness was controlled to be 30 μm (the mesh size of the screen printing screen was 200 mesh). The film was then sintered at 500 ° C in a muffle furnace for 1 hour, and then naturally cooled to room temperature to form a transparent TiO2 film, thereby obtaining the pretreated FTO glass.

[0057] The pretreated FTO glass was used as the deposition working electrode, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The three electrodes were placed in the deposition solution ({P2W 15 Cyclic voltammetry was performed on an electrochemical workstation in the voltage range of -1.0 V to 0.3 V (vs. Ag / AgCl) at a scan rate of 0.1 V / s for 30 cycles to deposit P2W on the FTO surface. 15 Nb3 thin film to obtain an electrochromic layer (EC layer).

[0058] After the deposition is completed, the surface of the electrochromic layer is cleaned with deionized water and then dried at 150° C. for 0.5 h to obtain a working electrode with a structure of FTO glass / electrochromic layer.

[0059] S2: Building an electrochromic smart window Dissolve Al(ClO4)3 and Zn(ClO4)2 in PC at a molar ratio of 1:1 and stir until completely dissolved to prepare a transparent liquid electrolyte with a concentration of 1 mol / L. Dry in a forced air drying oven at 50°C for 6 hours to remove moisture.

[0060] A liquid electrolyte was evenly applied to the electrochromic layer of the two working electrodes to form a coating. The two working electrodes were then placed parallel and facing each other, with the coatings in contact, to form an electrolyte layer. Two pieces of zinc foil were used as counter electrodes and inserted end-to-end into the electrolyte layer, horizontally relative to the EC layer (each zinc foil had a main section measuring 0.5 cm x 2 cm).

[0061] S3: External electrode formation and device packaging Copper foil conductive tape is pasted on the edge of the FTO glass to serve as a wire to lead out the positive and negative electrodes of the smart window. Copper foil conductive tape is also pasted on the extended section of the zinc foil. Finally, the entire smart window is encapsulated with epoxy resin to obtain an electrochromic smart window with a symmetrical electrode structure.

[0062] In the smart window of this embodiment, the sheet resistance of the FTO glass is 13 Ω / square, the thickness of the glass substrate is 2.2 mm, the thickness of the FTO conductive layer is 400 nm, and the electrochromic layer includes TiO2 microspheres and {P2W 15 The electrolyte layer is 2 mm thick and is a liquid electrolyte composed of Zn(ClO4)2 / Al(ClO4)3 and propylene carbonate. The zinc foil is 5 μm thick.

[0063] Figure 7 The SEM image of the electrochromic layer (EC layer) is shown. The left image shows the cross-sectional morphology, with the lower layer being FTO glass and the upper layer being the EC layer. The right image shows the surface morphology of the EC layer. As can be seen from the right image, the EC layer is formed by the accumulation of a large number of fine particles, with a loose and porous surface structure. This morphological feature facilitates electrolyte penetration and the exposure of active sites, meeting the structural requirements of an ideal electrochromic layer.

[0064] Figure 6 The figure shows the changes in the smart window during reversible conversion between colorless and blue (operating conditions: -1.4V for the device in the colored state and 1.8V for the device in the faded state), where the color display area is 2cm×2cm.

[0065] Comparative Example 1 The electrochromic smart window was prepared by referring to the method of Example 1, except that, when preparing the liquid electrolyte, lithium perchlorate in an equimolar amount (the sum of the zinc salt and the aluminum salt) was used as the electrolyte.

[0066] Comparative Example 2 The electrochromic smart window was prepared by referring to the method of Example 1, except that the polyacid {P2W 15 Nb3} is replaced by polyoxometalate {P5W 30} (Specifically K 12.5 Na 1.5 [NaP5W 30 O 110 ]·15H2O).

[0067] Comparative Example 3 An electrochromic smart window was prepared using the same method as in Example 1, except that the thickness of each electroluminescent layer was adjusted. Specifically, a TiO2 slurry was evenly coated onto the FTO conductive layer of the conductive glass using screen printing, with a wet film thickness of 3 μm (using a 420-mesh screen). The resulting film was then sintered in a muffle furnace at 500°C for 0.5 h and then naturally cooled to room temperature to form a transparent TiO2 thin film, thus obtaining pretreated FTO glass. The pretreated FTO glass was used as the deposition working electrode, and polyacid was deposited using the electrochemical deposition method described in Example 1 to obtain electrochromic layers. Each EC layer had a thickness of 500 nm.

[0068] Test Case The test examples are used to illustrate the electrochemical and optical properties of the electrochromic smart windows prepared in the above embodiments and comparative examples.

[0069] 1. Test methods for coloring voltage and fading voltage A step voltage was applied to the device using an electrochemical workstation (Shanghai Chenhua, model CHI 660E, the same below), and the color change of the device was observed to determine the voltage required to cause complete coloration (colorless → blue) and the voltage required to cause complete fading (blue → colorless).

[0070] 2. Impedance test: A three-electrode system was used, with the FTO glass / electrochromic layer of Example 1 as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl (3 M KCl) as the reference electrode. At open circuit potential, a sinusoidal AC disturbance signal with an amplitude of 5 mV was applied, with a frequency sweep range of 0.01 Hz to 10 6 Hz, the initial voltage was set to 0.05 V, and the test data were analyzed by fitting the equivalent circuit model using ZView software.

[0071] 3. Light transmittance test: Use a UV-Vis-NIR spectrophotometer (Hitachi UH4150) to test light transmittance, with a scanning range of 350-1300 nm.

[0072] 4. Cyclic stability test: The smart window was repeatedly switched between the tinting and fading voltages for multiple charge and discharge cycles. The transmittance change was monitored and the contrast retention rate (D) was calculated after 250 cycles at 650nm. The contrast retention rate (D) was calculated according to the following formula: D=(T n / T0)×100%, where T0 represents the initial contrast, T n The contrast obtained after 250 cycles is shown.

[0073] The results are shown in Table 1.

[0074] Table 1

[0075] Combining the data in Table 1, it can be seen from the comparison of Example 1 with Comparative Examples 1-3 that the smart window of Example 1 has a higher contrast and high cycle stability, and also has a lower operating voltage.

[0076] Figure 8 What is presented is P2W 15 The electrochemical impedance spectroscopy (EIS) of the Nb3 film in a liquid electrolyte (same composition as in Example 1) shows an incomplete semicircular feature in the high-frequency region, associated with the charge transfer process on the material surface; in the low-frequency region, an upward sloping line is observed, associated with the diffusion of ions within the film. This indicates that the film exhibits low internal resistance during redox reactions, which can improve its color change speed and reduce the voltage required for color change.

[0077] Figure 9 This is the cyclic voltammogram of the smart window in Example 1. As can be seen from the figure, when the operating voltage is -1.4V, the smart window can be transformed from a colorless and transparent state to a blue opaque state. When a voltage of 1.8V of the opposite polarity is applied, the smart window can return to its original colorless and transparent state.

[0078] Figure 10 The charge and discharge current curve of the smart window at 1mA charging current is shown in the figure. As can be seen from the figure, the discharge time of the smart window is 204s. After calculation, the area specific capacity of the device is 141mAh / m 2 , which shows that the smart window can not only adjust the color change, but also has the function of energy storage.

[0079] Figure 11 The transmittance curves of the smart window in both transparent and tinted states across the visible light spectrum are shown. Compared to traditional electrochromic smart windows made of inorganic materials (such as nickel oxide), the spectral response range of this smart window is broadened from 350–800 nm to 350–1300 nm. This allows optical modulation not only in the visible light band but also in the near-infrared band. At 850 nm, the transmittance of the smart window in the faded state is 86%, while the transmittance in the tinted state is 6%, resulting in an optical modulation value of 80%. At 1200 nm, the transmittance in the faded state is 96%, while the transmittance in the tinted state is 17%, resulting in an optical modulation value of 79%. This indicates that the smart window achieves a high optical modulation of approximately 80% in the near-infrared band (850–120 nm), demonstrating high contrast.

[0080] Figure 12 The optical response time of the device is shown. Combined with the figure, it is calculated that the fading time is 13s and the coloring time is 7s. It can be seen that the optical response of the smart window is relatively fast.

[0081] Figure 13 The cyclic stability of the smart window at a wavelength of 650nm is demonstrated. It is calculated that after 50,000 seconds of reversible conversion between colorless and blue (i.e., 250 cycles), it can still maintain 84% of its initial optical modulation amplitude.

[0082] In summary, the smart window of the present invention significantly broadens the spectral response range to the near-infrared band, so that it has the function of adjusting both visible light transmittance and near-infrared heat, and can achieve dual regulation of visible light and near-infrared heat in the solar spectrum. In addition, the smart window has a low operating voltage, high cycle stability and a high contrast. At the same time, the device can be used not only for display but also for energy storage, showing broad application prospects in the fields of building energy conservation, smart buildings, and improving indoor comfort.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. An electrochromic smart window, characterized in that: include: A first working electrode and a second working electrode are arranged opposite to each other, and an ion conductive medium layer is located therebetween; The first working electrode comprises a first transparent substrate, a first transparent conductive layer and a first electrochromic layer stacked in sequence; The second working electrode comprises a second transparent substrate, a second transparent conductive layer and a second electrochromic layer stacked in sequence; The ion conductive medium layer comprises: an electrolyte layer formed of a liquid electrolyte, the liquid electrolyte occupying a space between the first electrochromic layer and the second electrochromic layer and contacting the first electrochromic layer and the second electrochromic layer respectively; as well as a counter electrode, comprising two metal sheets, the two metal sheets being disposed at opposite ends of the electrolyte layer and spaced apart from each other, each metal sheet having a main section and an extension section, the main section being embedded within the electrolyte layer, and the extension section extending from the electrolyte layer; The first electrochromic layer and the second electrochromic layer both contain polyacids, and the polyacids are niobium-substituted heteropolytungstates; the liquid electrolyte contains aluminum salt and zinc salt.

2. The electrochromic smart window according to claim 1, characterized in that: The polyacid is K8H[P2W 15 (N b O2)3O 59 ]·12H2O; The thickness of the first electrochromic layer and the second electrochromic layer are independently 5 to 7 μm.

3. The electrochromic smart window according to claim 1 or 2, characterized in that: The first electrochromic layer and the second electrochromic layer further comprise TiO2 distributed in the layer.

4. The electrochromic smart window according to claim 1, characterized in that: The aluminum salt is aluminum perchlorate, and the zinc salt is zinc perchlorate; and / or The molar ratio of the aluminum salt to the zinc salt is 1:(0.8-1.2).

5. The electrochromic smart window according to claim 1 or 4, characterized in that: The liquid electrolyte further comprises an organic solvent, wherein the organic solvent is selected from at least one of propylene carbonate, ethylene carbonate and acetonitrile; In the liquid electrolyte, the total concentration of the aluminum salt and the zinc salt is 0.8-1.5 mol / L.

6. The electrochromic smart window according to claim 1, characterized in that: The first transparent substrate and the second transparent substrate are both glass; The materials of the first transparent conductive layer and the second transparent conductive layer are independently selected from at least one of indium tin oxide, fluorine-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide and antimony-doped tin oxide.

7. The electrochromic smart window according to claim 1, characterized in that: The thickness ratio of the first transparent substrate, the first transparent conductive layer and the first electrochromic layer is (200~400):(0.02~0.1):1; the thickness ratio of the second transparent substrate, the second transparent conductive layer and the second electrochromic layer is (200~400):(0.02~0.1):

1.

8. The electrochromic smart window according to claim 1, characterized in that: The thickness ratio of the ion conductive medium layer to the first working electrode is (0.5-1.5):

1.

9. The method for preparing the electrochromic smart window according to any one of claims 1 to 8, characterized in that: The steps include: (1) Preparation of the first working electrode and the second working electrode Providing a first transparent substrate having a first transparent conductive layer formed on its surface and a second transparent substrate having a second transparent conductive layer formed on its surface; applying a precursor solution containing the polyacid on the surfaces of the first transparent conductive layer and the second transparent conductive layer respectively to form a first electrochromic layer and a second electrochromic layer; (2) Constructing an ion conductive medium layer applying the liquid electrolyte on the surfaces of the first electrochromic layer and the second electrochromic layer respectively to form an electrolyte layer between the first electrochromic layer and the second electrochromic layer; A metal sheet is embedded in the opposite ends of the electrolyte layer respectively, so that each metal sheet has a main section and an extension section to obtain a counter electrode.

10. The preparation method according to claim 9, characterized in that Step (1) includes the following process: First, a TiO2 matrix layer is formed on the surface of the first transparent conductive layer and the second transparent conductive layer respectively to obtain a deposited working electrode; Then, each deposition working electrode is placed in a precursor solution containing polyacid, a voltage of -1V to 0.3V is applied, and a scanning speed of 0.05~0.1V / s is cyclically scanned for 10~50 times to deposit polyacid on the TiO2 matrix layer; wherein, The polyacid-containing precursor solution further comprises water and an electrolyte salt, wherein the electrolyte salt is selected from at least one of lithium perchlorate, lithium hexafluorophosphate, and lithium tetrafluoroborate; In the precursor solution containing the polyacid, the concentration of the polyacid is 0.5-2 mmol / L, and the concentration of the electrolyte salt is 0.05-2 mol / L.

Citation Information

Patent Citations

  • Polyacid-based pure inorganic multi-color electrochromic film

    CN104375349A

  • Electrochromic device based on polyoxometallate

    CN105629618A

  • Organic boric acid-rare earth-polyacid complexes as well as preparation method and application thereof in photoluminescent device

    CN109180711A

  • Double-electrochromic-layer device capable of realizing conversion between any colors and assembling method

    CN110928095A

  • Material for forming electrochromic film and its use

    JP1995003255A